The Significance of Incomplete Resection and Postoperative Pelvic Recurrence on the Prognosis of Rectosigmoid Cancer - Good, Roger R. (1986)
Ninety-eight patients underwent successful complete anterior or abdominoperineal resection for primary adenocarcinoma of the rectum, sigmoid, and rectosigmoid. At the time of diagnosis of relapse in 71 of these 98 patients, 36 patients had local-regional recurrence alone, without distant metastases. Twenty-two patients underwent curative resection and were classified with Dukes' stage D(1) lesions. The prognosis of these patients was similar to that of those who developed pelvic recurrence after initial complete resection. Of the 36 patients initially thought to have only localized pelvic recurrences, 15 patients (42 percent) subsequently developed overt distant metastases by the end of the study. Approximately one third (30 percent) of the 71 relapsed patients would have been potentially curable by new modalities currently under investigation by the authors—interstitial endocurietherapy (ECT) and intraoperative electron beam therapy (EBT).